KEANEKARAGAMAN JENIS MAMALIA DI HUTAN LARANGAN ADAT RUMBIO DESA RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Riri Syafni Marjuli; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Mammals is one of fauna who often have conflict with human and always made loss to both of them.Degradation can increase the possibility of the conflict. Prohibition forest of rumbio customary is one of forest had important mammals and no many data and information about the mammals. This research aimed to know species diversity and distribution of mammal in prohibition forest area of rumbio. This research done at December 2016. Mammals species diversity found 16 species from 10 families. Index species diversity of mammals in each region indicated that is Panoghan (H’=0.95), Sialang Layang (H’=1.64), Koto Naghao (H’=1.95) with mean 1.51. Species richness of mammals in panoghan (R1=3.22), Sialang Layang (R1=2.40), and Koto Kaghao (R1=2.56), and the mean is 2.72. Distribution of mammals at prohibition forest area of rumbio is random. Keywords: Mammals, biodiversity, prohibition forest area of rumbio